Assessing the Social Impact of Cotton Harvest Mechanization in Uzbekistan - Swinkels, Rob (World Bank E-Library Archive, 2016)
The Government of Uzbekistan (GoU) has recently adopted a policy to mechanize the cotton harvest as part of its drive to modernize the agricultural sector. Under Uzbekistan's state-order system it is compulsory for many farmers to grow cotton. They are contractually obligated to produce stipulated quantities that are annually set by the government, and must sell these to the GoU at a price fixed by the government. Almost all cotton in Uzbekistan is harvested by hand, even though mechanization existed during the Soviet period. An estimated 2.2-3 million